Diagnóstico del potencial endógeno de la Parroquia Rural de Jimbilla del Cantón Loja: periodo de estudio 2017 - 2018 - Jarro Macas, Karina Natali (2018)
This research titled "Diagnosis of the endogenous potential of Jimbilla, a rural parish of Loja's canton: study period 2017 - 2018", has as purpose to develop a diagnosis of the endogenous potential of the Parish; for that, first it was necessary the characterization of the endogenous development, and the identification of the resources considered as potential through the use of the PASC method. Finally, a proposal of endogenous development was made based on some dimensions that allow to improve the productive activity of the Parish. The importance of this research work lies in the fact that: through a study that determines the potentialities existing in the parish, is can lead to a proper use of the same, to achieve economic, social and productive growth that can improve the quality of life of its inhabitants. The study, it was determined that the endogenous potential ofthe Jimbilla parish is agricultural and tourist resources: in the agricultural field stands the cultivation of maize, vegetables, vegetables and blackberries; the raising of cattle, and the breeding of trout especially in the neighborhoods of Sevilla de Oro and Los Molinos; in terms of tourism, the use of the Shucos river stands out, which in recent years has become a place of recreation especially on dates such as carnival.